Validity and Reliability of the INSPIRE: Instrument Perceptions Science Inquiry and Nature of Science - Prelia Dwi Amanah; Thufail Mujjadid Al Qayyim; Muhammad Tantawi Jauhari; Eka Muliati; Fitratunisyah; A Wahab Jufri (International Journal of Contextual Science Education, 2025)
This research discusses about validity and reliability of teachers' perceptions of scientists, natural science (science) subjects, as well as the nature of science and scientific inquiry. The research was conducted by distributing questionnaires to science teachers in various regions for two weeks, which included 81 closed questions and 23 open questions. The results of the analysis show that the instruments used are valid and reliable, with the majority of teachers having a good understanding of the nature of science and the importance of science teaching. However, there is variation in perceptions regarding the characteristics of scientists and the effectiveness of inquiry methods. These findings highlight the need for ongoing professional development for teachers to improve the quality of science education. This research succeeded in developing and testing a valid and reliable INSPIRE instrument to measure science teachers' perceptions of scientists, science subjects, the nature of science (NOS), and the nature of scientific inquiry (NOSI). The research results show that this instrument can be used as an effective evaluation tool to understand teacher perceptions, which in turn can be a basis for designing more appropriate educational interventions.